2009
DOI: 10.1111/j.1365-2567.2009.03119.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to wounded tissue enhance cutaneous wound healing

Abstract: SummaryThe wound repair process is a highly ordered sequence of events that encompasses haemostasis, inflammatory cell infiltration, tissue regrowth and remodelling. Wound healing follows tissue destruction so we hypothesized that antibodies might bind to wounded tissues, which would facilitate the engulfment of damaged tissues by macrophages. Here, we show that B cells, which produce antibodies to damaged tissues, are engaged in the process of wound healing. Splenectomy delayed wound healing, and transfer of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 41 publications
4
59
1
Order By: Relevance
“…For example, we found that immunoglobulin heavy chain (a large polypeptide subunit of an antibody) was higher in bone samples in hibernating compared with active marmots. This is consistent with previous studies showing higher levels of immunoglobulin heavy chain in serum from hibernating compared with active bears (Chow et al 2013), which may possibly help explain bears' ability for wound healing during hibernation (Nishio et al 2009;Iaizzo et al 2012). Our finding is also consistent with increased numbers of B-lymphocytes in blood of hibernating 13-lined ground squirrels compared with active squirrels (Bouma et al 2013).…”
Section: Discussionsupporting
confidence: 93%
“…For example, we found that immunoglobulin heavy chain (a large polypeptide subunit of an antibody) was higher in bone samples in hibernating compared with active marmots. This is consistent with previous studies showing higher levels of immunoglobulin heavy chain in serum from hibernating compared with active bears (Chow et al 2013), which may possibly help explain bears' ability for wound healing during hibernation (Nishio et al 2009;Iaizzo et al 2012). Our finding is also consistent with increased numbers of B-lymphocytes in blood of hibernating 13-lined ground squirrels compared with active squirrels (Bouma et al 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Second, a large number of infiltrating B cells might be related with the pathogenesis of the cavity problem. B cells produce antibodies to damaged tissues, and are engaged in the process of wound healing [19]. As in recent observations, chronic inflammatory diseases such as the inflammatory bowel diseases and rheumatoid arthritis are characterized by a local accumulation of activated B cells [20,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…However, we indicated that T lymphocytes, usually predominant during the acute inflammatory process, were thought to produce several cytokines that enhance the proliferation of epithelial cells in cholesteatoma [13,15]. On the other hand, B cells produce antibodies in damaged tissues, and are engaged in the process of wound healing [19] and some chronic inflammatory diseases [20,21,22]. In this study, we also investigated the difference in the population of B and T lymphocytes between a cavity problem and cholesteatoma.…”
Section: Introductionmentioning
confidence: 99%
“…The immune system is composed of complex networks of molecules and cells that act together to orchestrate the beneficial inflammation needed to maintain and repair the body as well as to protect it from neoplastic cells and invading pathogens (1)(2)(3)(4)(5)(6). Abs binding to body molecules-autoantibodieswould appear to mark the self-reactivity needed for tissue healing (7) and for tumor surveillance (8); autoantibodies also mark autoimmune diseases (9). Thus, it would be important to investigate the characteristics of autoantibodies at birth in healthy humans as a starting point for subsequent evolution of the autoreactive repertoire.…”
mentioning
confidence: 99%